Asymmetric reinforcement in Lucania killifish: assessing reproductive isolation when both sexes choose. Issue 2 (30th November 2020) - St. John, Michelle E; Fuller, Rebecca C
Abstract: Reinforcement can occur when maladaptive hybridization in sympatry favors the evolution of conspecific preferences and target traits that promote behavioral isolation (BI). In many systems, enhanced BI is due to increased female preference for conspecifics. In others, BI is driven by male preference, and in other systems both sexes exert preferences. Some of these patterns can be attributed to classic sex-specific costs and benefits of preference. Alternatively, sex differences in conspecific preference can emerge due to asymmetric postzygotic isolation (e.g., hybrid offspring from female A × male B have lower fitness than hybrid offspring from female B × male A), which can lead to asymmetric BI (e.g., female A and male B are less likely to mate than female B and male A). Understanding reinforcement requires understanding how conspecific preferences evolve in sympatry. Yet, estimating conspecific preferences can be difficult when both sexes are choosy. In this study, we use Lucania killifish to test the hypothesis that patterns of reinforcement are driven by asymmetric postzygotic isolation between species. If true, we predicted that sympatric female Lucania goodei and sympatric male L. parva should have lower levels of BI compared with their sympatric counterparts, as they produce hybrid offspring with the highest fitness. To address the problem of measuring BI when both sexes are choosy, we inferred the contribution to BI of each partner using assays where one sex in the mating pair comes from an allopatric population with potentially low preference, whereas the other comes from a sympatric population with high preference. For one hybrid cross direction, we found that both female L. parva and male L. goodei have high contributions to BI in sympatry. In the other hybrid cross direction, we found that only female L. goodei contribute to BI. Sympatric male L. parva readily engaged in hybrid spawnings with allopatric L. goodei females. These results indicate that both asymmetric postzygotic isolation and the traditional sex-specific costs to preference likely affect the nature of selection on conspecific preferences and target traits.